Advocacy, support and survivorship in prostate cancer. (1st February 2017) - Dunn, J.; Casey, C.; Sandoe, D.; Hyde, M.K.; Cheron‐Sauer, M‐C.; Lowe, A.; Oliffe, J.L.; Chambers, S.K.
Abstract : Across Australia, prostate cancer support groups (PCSG) have emerged to fill a gap in psychosocial care for men and their families. However, an understanding of the triggers and influencers of the PCSG movement is absent. We interviewed 21 SG leaders (19 PC survivors, two partners), of whom six also attended a focus group, about motivations, experiences, past and future challenges in founding and leading PCSGs. Thematic analysis identified four global themes: illness experience; enacting a supportive response; forming a national collective and challenges. Leaders described men's feelings of isolation and neglect by the health system as the impetus for PCSGs to form and give/receive mutual help. Negotiating health care systems was an early challenge. National affiliation enabled leaders to build a united voice in the health system and establish a group identity and collective voice. Affiliation was supported by a symbiotic relationship with tensions between independence, affiliation and governance. Future challenges were group sustainability and inclusiveness. Study findings describe how a grassroots PCSG movement arose consistent with an embodied health movement perspective. Health care organisations who seek to leverage these community resources need to be cognisant of SG values and purpose if they are to negotiate effective partnerships that maximise mutual benefit.